The pollution status of the ship breaking area and its impact on tree growth and human health in Sitakunda, Bangladesh - Ali, Mohammed Khorshed; Jubaer, Ahmed; Talukder, Mohammed Anisuzzaman; Talukder, Mohammad Zahirul Islam; Zafar, Muhammad Tasneem; Islam, Sajia; Nahar, Ayesha Meherun; Sourav, Rubayat Tahrim (European Journal of Chemistry, 2024)
Chittagong Shipyard has been a source of pollution for the local ecosystem. From the shipyard, a substantial amount of pollutants is released into the environment during operations. Due to the release of heavy metals, chemicals, and oil into nearby water bodies, which subsequently contaminate the soil, pollution of both water and soil occurs. The pollution of air and water due to the burning of fuels and materials such as oil and paint has also slowed the growth of the plant. To evaluate the status of environmental pollution near the ship breaking industries in Sitakunda, several samples were collected and tested. The growth and yield performance of the Swietenia mahagoni Linn seedlings (Mahogani) was carried out in three different types of soil composition, such as nursery soil + shipyard soil, nursery soil + soil adjacent to the shipyard, and nursery soil + soil from a place away from the shipyard as a control in a ratio of 1:2. The seawater and soil samples collected from the three shipyards were found to be more polluted compared to those of the seawater and soil samples collected from an area away from the shipyards. The magnitude of pollution in different physical and chemical parameters of the seawater of the shipyard differs significantly (at p < 0.01) from the seawater away from the shipyard. The magnitude of pollution in different physical and chemical parameters of the shipyard soil differs significantly (at p < 0.05) from the soil adjacent to the shipyard and the soil away from the shipyard. The growth and yield of the Swietenia mahagoni Linn species were affected by growing on the shipyard soil with nursery soil. Total biomass production was minimum in seedlings grown in three different soils of shipyards, followed by seedlings grown in soil adjacent to the shipyards and seedlings grown in soil away from the shipyard.